MOTIVASI GUATEMALA MEMINDAHKAN KEDUTAAN BESAR KE YERUSALEM 2018 - Gevrazi "; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research describes about the foreign policy and decision making of a country that is identical with the consideration of national interests. By at the end of 2017 the US president made a policy against the UN Security Council resolution on the status of the Holy city of Jerusalem, the US determined Jerusalem to be the new capital of the state of Israel and moved the embassy there. Despite being opposed by the majority of UN member states, Guatemala became the first country to follow the US steps. The purpose of this research was to determine the motivation Guatemala move the embassy to Israel from Tel Aviv to Jerusalem in 2018. This research uses the perspective of realism, realism is a group that considers that the national interest is equated with an attempt to gain power that can be utilized to develop and maintain control of a country against another country to maintain the sovereignty of his country. This research uses foreign policy theory Richard Snyder's with the level of analysis of the nation state because in international relations it is nominated by the behavior of the nation-state. Based on this concept, national interests are considered as a means as well as a goal of a country to survive in the realm of international politics.The results of this research indicate that Guatemala's motivation to move the embassy to Israel to Jerusalem in 2018 was due to pressure from the legislative parliament, the background of decision maker President Jimmy Morales as an evangelical Christian, maintaining national interests against Israel by maintaining diplomatic relations with Israel as an ally with diplomatic relations which has been relatively good since 1948 and the United States is the largest provider of financial assistance to Guatemala every year and promotes Jewish lobbying organizations in the Central America region.Keywords: Policy, Foreign Policy, Embassy, Motivation, Jerusalem